Urban Planning for Immigrant Sustainability - Emília Malcata Rebelo (2004)
The main issue of this paper consists in the analysis of the relations between employment/unemployment, ethnic groups, and their residential and job locations, considering respective features. After an introduction and brief description of the main objectives of the project, a theoretical research is pursued on urban and economic planning sustainability, and its relations with immigrants and ethnic minorities. Then, a case study in Oporto Metropolitan Area (Portugal) is carried out, consisting in data collection, development and quantification of alternative explanatory variables, and development of a set of tools to support political decision making processes. An explanatory model is developed for dwelling location, expressed as a function of job spatial distribution and characteristics. Alternative policies are simulated through the model, and immediately displayed in a cartographic interface in geographic information systems. Finally, conclusions are pointed out and policy recommendations are proposed, applicable to other urban realities.